Pelatihan teknis persemaian, pembibitan, dan budidaya tanaman sayuran pada lahan tidur, Susweni - Manokwari Timur: Technical training on seedbeds, nurseries, and vegetable cultivation in undeveloped land, Susweni - East Manokwari - Taberima, Sartji; Prabawardani, Saraswati; Fenetiruma, Obadja; Mbusango, Amin; Mawikere, Nouke Lenda; Luhulima, Fiona Djunita Natalia (Fakultas Peternakan Universitas Papua, 2025)
ABSTRACT Susweni is one of the six villages located in East Manokwari District, Manokwari Regency, West Papua Province. Susweni village spans an area of 302,084 hectares and has a population of 725, indicating a significant amount of idle or undeveloped land that remains untapped for agricultural use. The agricultural sector plays a significant role in the lives of many people and is a central focus in national development, particularly in relation to the management and utilization of food commodities. The West Papua Provincial Agriculture and Food Crops Office, in partnership with the Agriculture Faculty, Papua University, aims to transform the undeveloped land in Susweni Village into productive land, with the goal of managing and utilizing this undeveloped land for productive agricultural purposes. We conducted technical guidance and plot demonstrations for six months, from June to November 2023, as part of the activity. On December 9, 2023, students and alumni from the Agriculture Faculty conducted a short training. They visited and learned how to cultivate vegetable crops, including seeding, transferring seedlings from the nursery into the land, and crop maintenance. The results demonstrated the successful growth and production of all crops, while the students and alumni, filled with enthusiasm, gained additional knowledge, skills, and experiences from this training. Keywords: Agricultural development; Idle land utilization; Susweni village; Technical guidance; Vegetable cultivation ABSTRAK Susweni merupakan salah satu dari enam kampung yang terletak di Distrik Manokwari Timur, Kabupaten Manokwari, Provinsi Papua Barat. Luas kampung Susweni adalah 302,084 ha, sedangkan jumlah penduduk 725 jiwa menunjukkan masih luasnya lahan-lahan tidur yang belum dimanfaatkan sebagai lahan produktif untuk sektor pertanian. Sektor pertanian memegang peranan penting untuk hayat hidup orang banyak dan merupakan salah satu sektor yang menjadi pusat perhatian dalam pembangunan nasional, khususnya yang berhubungan dengan pengelolaan dan pemanfaatan komoditas pangan. Dinas Pertanian Tanaman Pangan Provinsi Papua Barat bekerjasama dengan Fakultas Pertanian Universitas Papua berupaya menjadikan lahan tidur di Kampung Susweni sebagai lahan produktif yang bertujuan untuk mengelola dan memanfaatkan lahan tersebut untuk kawasan lahan pertanian yang telah diinisisasi pada tahun 2023. Metode kegiatan dalam bentuk bimbingan teknis dan demostrasi plot yang telah dilaksanakan selama lima bulan (Juni - November 2023) selama enam bulan, dan kunjungan PkM pada 09 Desember 2023. Kegiatan diikuti mahasiswa Faperta dan alumni Unipa. Hasil penyuluhan dan pendampingan selama enam bulan menunjukkan seluruh jenis tanaman sayuran tumbuh baik, dan peserta pelatihan sangat antusias dalam mengikuti pelatihan ini, dan mereka mendapatkan pengetahuan, keterampilan dan pengalaman dalam membudidayakan tanaman sayuran di Lahan Tidur Susweni. Kata kunci: Bimbingan teknis; Budidaya sayuran; Kampung Susweni; Pemanfaatan lahan tidur; Pengembangan pertanian